SHOT DOWN : THE POWERFUL STORY OF WHAT HAPPENED TO MH17 OVER UKRAINE AND THE LIVES OF THOSE WHO WERE ON BOARD - Velzen, Marianne Van (Crows Nest, New South Wales : Allen & Unwin, 2019)
On 17 July 2014, Malaysian Airlines MH17 was shot out of the sky above Ukraine. Aboard were 298 people, 38 of whom were Australians. No one survived. Subsequently it was shown that the airliner was almost certainly hit by a Buk surface-to-air missile fired by Ukrainian separatists aided by the Russian military. The debris from the plane's disintegration mid-air was spread over 50 square kilometres, but for weeks rescue teams and investigators were denied access. The Russians have refused to take any responsibility for the deaths. This is the story of some of the people who boarded that fatal flight and the conflict below them that was doomed to destroy their lives and the happiness of the people they left behind. The fullest account yet published, it is also the story of a continuing clamour for justice. Unsettling, compelling and revealing, Shot Down will provoke both outrage that this criminal act could have happened and deep sadness for the lives lost.
Map: Route taken by MH17Map: MH17 debris sites-- Chapter 1 Amsterdam, 17 July 2014-- Chapter 2 Ukraine, November 2013-- Chapter 3 17 July 2014-- Chapter 4 Ukraine, November-December 2013-- Chapter 5 17 July 2014-- Chapter 6 Ukraine, January-March 2014-- Chapter 7 17 July 2014-- Chapter 8 Crimea, February-March 2014-- Chapter 9 17 July 2014-- Chapter 10 Ukraine, March 2014-- Chapter 11 17 July 2014-- Chapter 12 Ukraine, June-July 2014 -- Chapter 13 17 July 2014-- Chapter 14 Ukraine, 17 July 2014-- Chapter 15 17 July 2014-- Chapter 16 Chaos-- Chapter 17 Outrage-- Chapter 18 Bringing them home-- Chapter 19 The Buk-- Chapter 20 The wreckage-- Chapter 21 2015-- Chapter 22 2016-- Chapter 23 2017-- Chapter 24 2018-- Chapter 25 Empty chairs.
Includes bibliographical references.
Keywords: Malaysia Airlines Flight 17 Crash, Ukraine, -- 2014; Aircraft accidents -- Investigation -- Ukraine; Aircraft accident victims -- Ukraine